Implementasi model pembelajaran discovery learning untuk meningkatkan hasil belajar mahasiswa pada materi reading comprehension - Susanti, Susanti (Nur Science Institute, 2025)
This study examines the effectiveness of the discovery learning model in improving students’ learning outcomes in reading comprehension. The background of the study stems from students' low reading comprehension skills, largely due to the dominance of conventional teaching methods that lack critical thinking engagement. Using a quantitative approach with a quasi-experimental design (pretest-posttest control group), the study involved 60 fourth-semester students divided into experimental and control groups. Data were collected through reading comprehension tests and observations of learning activities, then analyzed using descriptive and inferential statistics, including t-tests. The results showed a significant improvement in the experimental group compared to the control group. These findings demonstrate that discovery learning is effective in enhancing reading comprehension and learning engagement, and contributes to the development of innovative instructional models in higher education.